Knowledge and perceptions about clinical research and its ethical conduct among college students from non-science background: a representative nation-wide survey from India - Jeffrey Pradeep Raj; Suraj Kallarakal Tomy; Amrutha Jose; Aadrika Kashyap; Joseph Varghese Kureethara; Tomy K Kallarakal (BMJ Public Health)
Introduction Prior studies on public attitudes and awareness of clinical research (CR) in India before the pandemic identified significant knowledge gaps. Thus, we aim to investigate if the pandemic has influenced awareness and attitudes towards CR given the wide mass and social media coverage on drug/vaccine development process.Methods This was an online survey conducted among young adults enrolled as students in a university in south India between 15 September 2022 and 31 October 2022. Until recently, these students attended online classes from various locations across India, likely reflecting a diverse regional and traditional background. Information regarding their sociodemographic status, awareness and perception about CR was collected and analysed applying the principle of descriptive and inferential statistics.Results A total of N=4796 eligible survey responses were analysed. Approximately, 50% were unfamiliar with CR but 42.4% expressed willingness to participate in a future CR. The significant predictors for a higher favourable perception score were having heard about CR (p<0.001), known exactly what a CR means (p<0.001) and having known anyone who participated in a CR (p<0.001). The significant predictors for willingness to participate in a CR were those living in villages as against those living in cities (p=0.002), belongs to Brahm Govind (BG) Prasad’s socioeconomic status class 1 (p=0.023) or class 4 (p=0.011) as against those in class 5, those who have heard about CR (p=0.023), participated in CR (p<0.001), have known someone participated in a CR (p<0.001) or higher total score of favourable perceptions (p<0.001).Conclusions While there was extensive media coverage on drug/vaccine development processes during the COVID-19 pandemic, significant knowledge gaps and concerns regarding various aspects of CR persisted. Although some individuals showed a positive view of CR and its societal benefits, the overall public awareness remains insufficient.